2020
DOI: 10.1007/s42399-020-00546-z
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 Outbreak: an Epidemiological and Clinical Perspective

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak started with the detection of an increasing number of pneumonia cases of unknown origin in Wuhan, China, since December 2019. The disease caused by SAS-CoV-2 was subsequently named coronavirus disease 2019 (COVID-19). Currently, the ongoing COVID-19 pandemic poses a global health concern with more than 28.9 million confirmed cases, taking away the lives of more than 900,000 people worldwide. To prevent further spread of the disease, an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…In severe cases, it could lead to pneumonia, respiratory failure, cardiac arrest and death. 9 However, it is estimated that 30% and up to 70% of patients in some studies could have the virus without showing symptoms of the disease, 10–15 impacting on the control of the pandemic. Currently, preventive measures including social distancing, regular hand sanitization, regularly wiping surfaces, quarantining and the wearing face masks are the most effective methods to reducing the spread of the virus and its subsequent morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, it could lead to pneumonia, respiratory failure, cardiac arrest and death. 9 However, it is estimated that 30% and up to 70% of patients in some studies could have the virus without showing symptoms of the disease, 10–15 impacting on the control of the pandemic. Currently, preventive measures including social distancing, regular hand sanitization, regularly wiping surfaces, quarantining and the wearing face masks are the most effective methods to reducing the spread of the virus and its subsequent morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 COVID-19 is a pulmonary disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which belongs to the Coronaviridae family. 5,6 Coronaviruses contain a single-stranded RNA genome ranging from 25 to 32 kilobases and are generally categorized into four major genera: alpha-, beta-, gamma-, and delta-coronavirus. 7,8 SARS coronavirus caused an outbreak in 2002, resulting in more than 8,000 infections and 774 deaths across 37 countries.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no effective methods have been found that can prevent the spread of the epidemic, apart from emphasizing the need for extended social distancing, molecular/antibody testing for infections, and contact tracing to identify and isolate infected patients. 5,21 In addition, antibody testing can be applied to identify individuals with previous SARS-CoV-2 infection, and those former patients with sufficient convalescent plasma may opt to donate blood to benefit the therapy of current patients. At the community level, antibody surveillance programs can be implemented to locally monitor public serological data to better inform public health policy, while increased molecular testing can be used to evaluate the efficacy of vaccination efforts.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 is a highly contagious virus that has led to a worldwide epidemic; it causes fever, headache, cough, myalgia, fatigue, sputum production, and hemoptysis (Chen et al, 2020;Huang et al, 2020; Coronaviridae Study Group of the International Committee on Taxonomy of V, 2020; Wong, 2020;Wu and McGoogan, 2020;Xu J. et al, 2020). Most patients infected with SARS-CoV-2 can develop acute respiratory distress syndrome (ARDS) (Zumla et al, 2020).…”
Section: Introductionmentioning
confidence: 99%